Rethinking Brain Death as a Legal Fiction: Is the Terminology the Problem? - Shah, Seema K. (The Hastings Center report, 2018)
Brain death, or the determination of death by neurological criteria, has been described as a legal fiction. Legal fictions are devices by which the law treats two analogous things (in this case, biological death and brain death) in the same way so that the law developed for one can also cover the other. Some scholars argue that brain death should be understood as a fiction for two reasons: the way brain death is determined does not actually satisfy legal criteria requiring the permanent cessation of all brain function, and brain death is not consistent with the biological conception of death as involving the irreversible cessation of the functioning of an organism as a whole. Critics counter that the idea that brain death is a legal fiction is deceptive and undemocratic. I will argue that diagnosing brain death as a hidden legal fiction is a helpful way to understand its historical development and current status. For the legal-fictions approach to be ethically justifiable, however, the fact that brain death is a legal fiction not aligned with the standard biological conception of death must be acknowledged and made transparent.